1972
DOI: 10.1113/jphysiol.1972.sp009861
|View full text |Cite
|
Sign up to set email alerts
|

The role of the solitary and paramedian reticular nuclei in mediating cardiovascular reflex responses from carotid baro‐ and chemoreceptors

Abstract: SUMMARY1. With dye-filled micro-electrodes single neurones in the medulla of anaesthetized paralysed cats were identified which: (a) fired rhythmically in synchrony with or were modulated by the cardiac cycle, and which ceased firing with occlusion of the ipsilateral common carotid artery (carotid sinus baroreceptor neurones); (b) were excited by stimulation of carotid body chemoreceptors by close intra-arterial injection of lobeline into the thyroid artery (carotid body chemoreceptor neurones).2. Twelve carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(59 citation statements)
references
References 44 publications
1
58
0
Order By: Relevance
“…It is well known that hypoxic chemoreflex activation evokes baroreflex inhibition attributed to central nervous system modulation at the level of the nucleus of the solitary tract. 42,43 The hypertension induced by CIH is associated with reduced BRS efficiency in adult animals exposed to CIH for 1 to 3 months, 9,[11][12][13][14]40,41,44 but other studies performed in juvenile rats have shown that juvenile rats exposed to CIH for 15 days showed an increased cardiac baroreflex gain associated with a rightward shift on the operating point to higher pressures, as related to control rats. 38 Zoccal et al 38 proposed that the sympathetic-mediated hypertension is not secondary to a reduction in cardiac baroreflex gain, but to an enhanced respiratory-sympathetic coupling.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that hypoxic chemoreflex activation evokes baroreflex inhibition attributed to central nervous system modulation at the level of the nucleus of the solitary tract. 42,43 The hypertension induced by CIH is associated with reduced BRS efficiency in adult animals exposed to CIH for 1 to 3 months, 9,[11][12][13][14]40,41,44 but other studies performed in juvenile rats have shown that juvenile rats exposed to CIH for 15 days showed an increased cardiac baroreflex gain associated with a rightward shift on the operating point to higher pressures, as related to control rats. 38 Zoccal et al 38 proposed that the sympathetic-mediated hypertension is not secondary to a reduction in cardiac baroreflex gain, but to an enhanced respiratory-sympathetic coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Different reports have shown that the nTs receives inputs from baroreceptor (Crill and Reis, 1968; Miura and Reis, 1972;Berger, 1979;Kalia and Welles, 1980;Sawchenco and Swanson, 1981), re spiratory (von Euller et a!., 1973), gustatory (Blom-visualization of nerve terminations throughout the brain stem. Pretreatment with capsaicin reduced the density of labeled neurons and terminals within the trigeminal gan glion and the brain stem, respectively, following WGA HRP application over the middle cerebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial baroreceptor sensitivity is impaired because of chronic cyclosporine uptake. 29 The close proximity of baroreceptor and chemoreceptor neurons in the solitary and paramedian reticular nuclei in the medulla could explain the interactions between these reflexes 30,32 ; however, such an interference between baroreceptors and central chemoreceptors has not been described. Thus, although the surgical procedure improves cardiac function, which may favor normalization of central chemoreceptor sensitivity, it also alters inhibitory loops and necessitates drug treatments, which may suppress baroreflex restraint on peripheral chemoreflex control.…”
Section: Central Chemoreflex Sensitivitymentioning
confidence: 99%